In vitro digestibility of gels from different starches: Relationship between kinetic parameters and microstructure. (November 2021) - Aleixandre, Andrea; Benavent-Gil, Yaiza; Moreira, R.; Rosell, Cristina M.
Abstract: Starch performance along digestion is becoming of utmost importance owing to the extensive presence of starch in foods and its association to the foods glycaemic index. However, scarce information exists on the relationship between the digestibility of starch gels and their microstructure. The aim of the study was to identify the rate and degree of digestion of starch gels from different botanical sources and the impact of gels microstructure with the in vitro starch digestibility (IVSD) by fitting the hydrolysis kinetics. Starch gels from cereals, tubers, and pulses were structurally analyzed and subjected to a standardized oro-gastrointestinal IVSD. The gel microstructure was significantly different among starches. Cereal gels had thinner walls than tuber and pulses gels, and this discrimination was not evident in the area of the gel cavities. Starches hydrolysis was well fitted to a first-order kinetics model, except for rice starch gel. Potato and chickpea gels showed the slowest digestion, and in the case of potato gel some starch remained undigested at the end of the digestion. The amylose content of gels was correlated with starch hydrolysis rate. Moreover, starch gels with thinner walls and/or bigger cavities seems to facilitate the enzyme action, and therefore, the starch digestibility. Graphical abstract: Image 1 Highlights: Starch gels from different sources show different microstructures. Gel microstructure may affect starch digestibility. Amylose content plays an important role in gel in vitro digestibility. Kinetics models of starch gels digestibility discriminate among starch sources.